Improvisation and Hybrid Genres: Reading Childe Harold's Pilgrimage. Issue 3 (19th May 2019) - Beatty, Bernard
ABSTRACT: In the first section I ask two questions: what sort of a poem is Childe Harold's Pilgrimage, and what is the immediate experience of reading it in sequence? These two questions are the practical equivalents of the main terms of my title. I try to answer them by reconstructing a first reading of the poem in the light of my own experience and the imagined one of the first readers of the poem. I suggest that two terms—accretion and elimination—are helpful here and that, in some ways, the structure and sequential experiencing of the poem resemble the structures of extended nineteenth-century musical forms. In the second section, I reverse perspective and take a position at the end of the poem. From such a point, it is easier to find what the poem has included and eliminated and this, in turn, suggests the kind of poem that it is. In the third section I tackle the terms "improvisation" and "hybrid genres" directly, link them with my earlier arguments, and engage with some theorists, especially Bakhtin. In particular, I argue against the view that Childe Harold's Pilgrimage dissolves genre but argue that genres are nevertheless "open categories." My conclusion is less definite. I confess to difficulties that still bother me.